Comparative study of Ga and Al alloying with ZrFe2 for high-pressure hydrogen storage. (29th March 2022) - Qin, Changsheng; Wang, Hui; Jiang, Wei; Liu, Jiangwen; Ouyang, Liuzhang; Zhu, Min
Abstract: ZrFe2 reacts reversibly with hydrogen under extremely high hydrogen pressure and shows potential for high-pressure hydrogen compression and storage. Alloying is indispensable to tune its hydrogen storage properties for practical applications. Previous works indicated that the Al substitution for Fe would drastically decrease hydrogen storage capacity. This work used the quenching process to prepare the ZrFe2- x Al x and ZrFe2- x Ga x (0.1 ≤ x ≤ 0.2) alloys with a single C15 Laves phase structure. It was found that the presence of the second phase Zr2 Fe in as-cast alloys is responsible for the capacity reduction. The quenched ZrFe1.9 Al0.1 alloy delivers a maximum hydrogen storage capacity of 1.79 wt%, much higher than as-cast alloys. The comparative study further shows that ZrFe2- x Ga x alloys have a relatively higher equilibrium pressure than ZrFe2- x Al x alloys due to a higher bulk modulus for ZrFe2- x Ga x alloys by the theoretical calculations. The hydrogen storage performance test indicates that the hydrogen dissociation pressure of ZrFe1.9 Ga0.1 and ZrFe1.9 Al0.1 is 164.0 atm and 130.7 atm at 298 K, respectively. Our work demonstrates that ZrFe2 -based alloys with a small Ga or Al substitution are suitable for high-pressure hydrogen storage applications. Graphical abstract: Image 1 Highlights: Al and Ga substitutions could modify the hydrogen storage properties of ZrFe2 . The quenching process could remove the Zr2 Fe impurity in as-cast Zr-Fe-Al alloys. The quenched ZrFe1.9 Al0.1 alloy delivers a maximum hydrogen storage capacity of 1.79 wt%. The desorption plateau pressure of ZrFe1.9 Ga0.1 and ZrFe1.9 Al0.1 at 298 K is 164.0 and 130.7 atm, respectively.